2020
DOI: 10.1001/jamanetworkopen.2020.14736
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Distribution, and Lethality of Firearm Injuries in California From 2005 to 2015

Abstract: Key Points Question What were the trends and distributions of nonfatal firearm injuries and how lethal were firearm injuries in California from 2005 to 2015? Findings This serial cross-sectional study including 81 085 firearm-related emergency department visits and hospitalizations found that nonfatal firearm injuries decreased by 38.1% between 2005 and 2015, driven by a 46.4% decrease in assaultive injuries; self-inflicted injuries decreased by 13.4% and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…24 Firearms are associated with a particularly high case fatality ratio compared to poisonings and other methods of suicide, and therefore, warrant further inspection of their influence on physician suicide. 25 Our study found that firearms were the most commonly used lethal method by all physicians and surgeons. A recent 2020 study found that firearm ownership was associated with substantially elevated risk of suicide by firearm, with hazard ratios of 7.82 for men and 35.15 for women.…”
Section: Discussionmentioning
confidence: 69%
“…24 Firearms are associated with a particularly high case fatality ratio compared to poisonings and other methods of suicide, and therefore, warrant further inspection of their influence on physician suicide. 25 Our study found that firearms were the most commonly used lethal method by all physicians and surgeons. A recent 2020 study found that firearm ownership was associated with substantially elevated risk of suicide by firearm, with hazard ratios of 7.82 for men and 35.15 for women.…”
Section: Discussionmentioning
confidence: 69%
“…County-level denominators came from annual American Community Survey (ACS) population data. 15 To maximize exchangeability, we included county-level factors associated with firearm violence, identified a priori based on prior studies, [16][17][18][19] in the synthetic control model. These included percentage of residents aged 15 to 24 years and 55 years and older; percentage Hispanic, non-Hispanic Black, and non-Hispanic White residents; and percentage men; nonfirearm violent crime and property crime rates per 1000 residents; handgun sales per 1000 residents; unemployment in the civilian population aged 16 years and older; and urbanicity (eMethods in the Supplement).…”
Section: Data and Measuresmentioning
confidence: 99%
“…Handgun acquisition has been associated with large increases in firearm suicide risk, with a hazard ratio of nearly 8 among men and over 35 among women (Studdert et al 2020 ). Despite this purchasing surge and the high lethality of firearm suicide attempts (Conner et al 2019 ; Spitzer et al 2020 ), few studies have examined pandemic-era trends in firearm suicide specifically, and none have looked at California, the most populous and diverse state in the USA.…”
Section: Introductionmentioning
confidence: 99%